Inflammation in Diabetic Nephropathy - Andy K. H. Lim; Gregory H. Tesch (Mediators of Inflammation)
Diabetic nephropathy is the leading cause of end-stage kidney disease worldwide but current treatments remain suboptimal. This review examines the evidence for inflammation in the development and progression of diabetic nephropathy in both experimental and human diabetes, and provides an update on recent novel experimental approaches targeting inflammation and the lessons we have learned from these approaches. We highlight the important role of inflammatory cells in the kidney, particularly infiltrating macrophages, T-lymphocytes and the subpopulation of regulatory T cells. The possible link between immune deposition and diabetic nephropathy is explored, along with the recently described immune complexes of anti-oxidized low-density lipoproteins. We also briefly discuss some of the major inflammatory cytokines involved in the pathogenesis of diabetic nephropathy, including the role of adipokines. Lastly, we present the latest data on the pathogenic role of the stress-activated protein kinases in diabetic nephropathy, from studies on the p38 mitogen activated protein kinase and the c-Jun amino terminal kinase cell signalling pathways. The genetic and pharmacological approaches which reduce inflammation in diabetic nephropathy have not only enhanced our understanding of the pathophysiology of the disease but shown promise as potential therapeutic strategies.